A Comparative Analysis of Child Custody and Access Rights After Divorce or Separation in Kenya and England - Kenneth, Kaunda Kodiyo (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
This study examines the laws and practices surrounding child custody and access rights in Kenya and England following divorce or separation. Its goal is to identify similarities and differences in both countries' legal frameworks and social practices governing these issues. The research methodology employed for this study includes reviewing existing literature such as statutes, case law, and academic papers. The study has discovered that while there are some similarities in the legal frameworks governing child custody and access rights in Kenya and England, there are also significant differences in the legal principles and social practices that inform these frameworks. Various factors, including cultural norms, socioeconomic status, and the role of the family in society, influence these differences. In conclusion, the study suggests that further research is necessary to understand how these differences affect parents and children in both jurisdictions. Additionally, it recommends developing more effective legal and social policies to support families after divorce or separation.